Optimalisasi Sosialisasi Manfaat Program BPJS Ketenagakerjaan untuk Meningkatkan Brand Knowledge kepada Pelajar dan Mahasiswa Kota Surabaya - Mayhana Dwi Novitasari; Siti Aminah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
National social security exists to provide welfare for the people of Indonesia. The many occupational risks that occur have led to the establishment of the Employment Social Security Administration Agency (BPJS Ketenagakerjaan) as a form of social security provided by the state to protect workers. The lack of public knowledge raises understanding and makes people not want to enjoy it, even though the benefits provided are enormous. The owners of the rights to BPJS Ketenagakerjaan benefits are not only formal workers, but informal workers are also entitled to receive them; even apprentices and community service program participants also have the right to this protection. So that it is necessary to increase the brand knowledge of the BPJS Ketenagakerjaan in the community so that there are no misunderstandings. By optimizing the socialization of the benefits of the BPJS Ketenagakerjaan program, we can accelerate brand knowledge and grow brand awareness.